2021
DOI: 10.3389/fimmu.2021.642127
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Cellular Therapies for Anti-myeloperoxidase Vasculitis and Other Autoimmune Diseases

Abstract: Anti-myeloperoxidase vasculitis (MPO-AAV) is a life-threatening autoimmune disease which causes severe inflammation of small blood vessels, mainly in the kidney. As for many other autoimmune diseases, current treatments, which consist of general immunosuppressants, are partially effective, toxic and broadly immunosuppressive, causing significant and serious adverse effects in many patients. Therefore, there is an urgent need for more targeted and less harmful therapies. Tolerogenic dendritic cells, regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 115 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…However, further HLA genotyping and association studies in a larger number of samples may reveal a relationship between the HLA haplotype and diabetes risk. MPO-AAV is a life-threatening autoimmune disease which causes severe inflammation and destruction of small blood vessels, mainly in the kidneys of people older 50 years 33 . Given that neuroinflammation significantly contributes to the onset and progression of LOAD 10 , 13 , this result suggests that the presence of the DRB1*09:01-DQB1*03:03 haplotype might confer an increased risk of LOAD, even in adults without the APOE 4 allele.…”
Section: Discussionmentioning
confidence: 99%
“…However, further HLA genotyping and association studies in a larger number of samples may reveal a relationship between the HLA haplotype and diabetes risk. MPO-AAV is a life-threatening autoimmune disease which causes severe inflammation and destruction of small blood vessels, mainly in the kidneys of people older 50 years 33 . Given that neuroinflammation significantly contributes to the onset and progression of LOAD 10 , 13 , this result suggests that the presence of the DRB1*09:01-DQB1*03:03 haplotype might confer an increased risk of LOAD, even in adults without the APOE 4 allele.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated levels of MPO have been detected in atherosclerotic lesions, and studies suggest that it may serve as a marker for increased cardiovascular risk. MPO is considered a potential biomarker for assessing inflammation and oxidative stress associated with atherosclerosis, and its measurement in blood samples is being explored in clinical research [79,80].…”
Section: Biomarkers In Atherosclerosismentioning
confidence: 99%
“… 194 Emerging cell therapies with tolerogenic dendritic cells, regulatory T cells (CAR-T cells), and stem cells (namely human amniotic epithelial cells) will probably emerge due to their selective immunosuppressive capacity. 195 In addition, the use of cytokines for the treatment of autoimmune rheumatic diseases has been studied. 196 It was shown that administration of low dose IL-2 allows expansion of T reg repertoire without effector T cell activation.…”
Section: Treatmentmentioning
confidence: 99%